Desenvolvimento de um plano de manutenção e reabilitação das vias da cidade de Caraúbas/RN - Oliveira, Felipe Augusto Dantas de (Universidade Federal Rural do Semi-Árido, 2018)
One of the main steps for the good performance of an Pavement Management System for Urban Road (PMSUR) is to obtain data with sufficient information to characterize the surface condition of the roads evaluated. Based on the characterization of the current state of the road network, it is possible to prioritize the priority pathways that must be met in relation to the maintenance and rehabilitation processes, assisting the administration in the decision making process, in order to direct public resources more effectively, ensuring the best cost-benefit ratio. Thus, the present work aims to use free software and tools to develop a maintenance and rehabilitation plan for the asphalt roadways in the city of Caraúbas/RN. Approximately 11km of the 72 km are constituted by roads with asphaltic pavement. In a sample form (10% of the total extension), representative sections of each paved road were chosen for the evaluation of its surface condition, using the IGG (Global Severity Index), IES (Surface State Index) and IRI (Longitudinal Irregularity Index). Soon after, it was possible to determine the type of maintenance and rehabilitation for each route evaluated from the level of functionality of the evaluated sections, in addition to generating a tree of choice to select the alternative of maintenance or rehabilitation. Finally, a method of hierarchizing priority routes was developed in relation to the sections with greater and lesser need for maintenance, taking into account the technical, economic and traffic characteristics for each stretch, to highlight the most and least stretches critical decision-making, serving as decision-making aid for the competent authorities. In general, it was observed that with the help of the objective methods developed here it was possible to determine the maintenance or rehabilitation alternative for all the evaluated sections, as well as to classify them in more and less critical stretches, besides estimating the cost in (km) for each of them.
Monografia
Keywords: Gerência de pavimentos; Pavimentos urbanos; Manutenção; Índice de prioridade; ENGENHARIAS::ENGENHARIA CIVIL